Near-precise interchromosomal recombination and functional DNA topoisomerase II cleavage sites at MLL and AF-4 genomic breakpoints in treatment-related acute lymphoblastic leukemia with t(4;11) translocation - Lovett, Brian D. (National Academy of Sciences, 2001)
We analyzed the der(11) and der(4) genomic breakpoint junctions of a t(4;11) in the leukemia of a patient previously administered etoposide and dactinomycin by molecular and biochemical approaches to gain insights about the translocation mechanism and the relevant drug exposure. The genomic breakpoint junctions were amplified by PCR. Cleavage of DNA substrates containing the normal homologues of the MLL and AF-4 translocation breakpoints was examined in vitro upon incubation with human DNA topoisomerase IIα and etoposide, etoposide catechol, etoposide quinone, or dactinomycin. The der(11) and der(4) genomic breakpoint junctions both involved MLL intron 6 and AF-4 intron 3. Recombination was precise at the sequence level except for the overall gain of a single templated nucleotide. The translocation breakpoints in MLL and AF-4 were DNA topoisomerase II cleavage sites. Etoposide and its metabolites, but not dactinomycin, enhanced cleavage at these sites. Assuming that DNA topoisomerase II was the mediator of the breakage, processing of the staggered nicks induced by DNA topoisomerase II, including exonucleolytic deletion and template-directed polymerization, would have been required before ligation of the ends to generate the observed genomic breakpoint junctions. These data are inconsistent with a translocation mechanism involving interchromosomal recombination by simple exchange of DNA topoisomerase II subunits and DNA-strand transfer; however, consistent with reciprocal DNA topoisomerase II cleavage events in MLL and AF-4 in which both breaks became stable, the DNA ends were processed and underwent ligation. Etoposide and/or its metabolites, but not dactinomycin, likely were the relevant exposures in this patient.